For another school: provocations to didactis and pedagogical innovation concept - Vasconcellos, Mônica; Maciel, Sandra (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2019)
Identifying elements pointing basic education and innovative pedagogical perspectives from undergraduates and teachers perspective is the aim of this study, resulting in teaching staff reflections by UFF Center for Teaching and Training of Teachers and qualitative evaluations carried out with students of Didactic Discipline. It promoted a (re)approximation with the school, generating individual records and interviews with basic school teachers, considered innovative by the graduates. In contrast to linking the concept of pedagogical innovation to technological apparatuses insertion, the fellow students expressed preoccupations with a more fair society construction, based on aspects such as teaching autonomy, dialogue, commitment and creativity. The political and social school recognition  is the main locus of human formation and community, reflecting urgency on other scholar thinking and conducting ways are perspectives of the present discussion